In the name of democracy : JP movement and the emergency - Chandra, Bipan (Penguin Books, 2003)
On the movement by Jai Prakash Narain for the ouster of prime minister Indira Gandhi, 1917-1984, which led to the imposition of internal emergency in India, June 1975-January 1977.